From Cherries to Cherries - Boršková, Jana (Czech Republic, 2011)
This film is about the director's mother authentically captures the year in the family's life following the father's death and raising fundamental questions on the subject of love in family relationships
Verzio Film Festival Submission
Keywords: Documentary films